Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1038/s41586-023-05737-x
|View full text |Cite
|
Sign up to set email alerts
|

Four ways blue foods can help achieve food system ambitions across nations

Abstract: Blue foods, sourced in aquatic environments, are important for the economies, livelihoods, nutritional security and cultures of people in many nations. They are often nutrient rich1, generate lower emissions and impacts on land and water than many terrestrial meats2, and contribute to the health3, wellbeing and livelihoods of many rural communities4. The Blue Food Assessment recently evaluated nutritional, environmental, economic and justice dimensions of blue foods globally. Here we integrate these findings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 101 publications
1
19
0
Order By: Relevance
“…Recent, in-depth, global reviews of the rapid progress of aquaculture over the past decade toward increased environmental responsibilities and resource conservation (Boyd et al, 2020;Naylor et al, 2021) lay a new foundation for aquaculture's future contributions to the SDGs (Troell et al, 2023). The potential of aquaculture development throughout the world at all scales is now included in the assessments of the future of aquatic food or "blue foods", or in a "blue transformation", by international agencies, university centers, governments, nongovernmental and philanthropic organizations (CEA Consulting, 2020;Crona et al, 2023;Costello et al, 2019;FAO, 2022c;HLPE, 2014;Hoegh-Guldberg et al, 2019;O'Shea et al, 2019;SAPEA, 2017;Stuchtey et al, 2020). Transdisciplinary assessments of both fed and unfed aquaculture systems have shown that many types of aquaculture systems produce products of higher nutritional values and altogether aquaculture accounted for less than 1% of anthropogenic greenhouse gas (GHG) emissions in 2017, similar to emissions from sheep production (Gephart et al, 2016(Gephart et al, , 2021Hallström et al, 2019;MacLeod et al, 2020).…”
Section: The Role Of Aquaculture In Sustainable Development and Globa...mentioning
confidence: 99%
“…Recent, in-depth, global reviews of the rapid progress of aquaculture over the past decade toward increased environmental responsibilities and resource conservation (Boyd et al, 2020;Naylor et al, 2021) lay a new foundation for aquaculture's future contributions to the SDGs (Troell et al, 2023). The potential of aquaculture development throughout the world at all scales is now included in the assessments of the future of aquatic food or "blue foods", or in a "blue transformation", by international agencies, university centers, governments, nongovernmental and philanthropic organizations (CEA Consulting, 2020;Crona et al, 2023;Costello et al, 2019;FAO, 2022c;HLPE, 2014;Hoegh-Guldberg et al, 2019;O'Shea et al, 2019;SAPEA, 2017;Stuchtey et al, 2020). Transdisciplinary assessments of both fed and unfed aquaculture systems have shown that many types of aquaculture systems produce products of higher nutritional values and altogether aquaculture accounted for less than 1% of anthropogenic greenhouse gas (GHG) emissions in 2017, similar to emissions from sheep production (Gephart et al, 2016(Gephart et al, , 2021Hallström et al, 2019;MacLeod et al, 2020).…”
Section: The Role Of Aquaculture In Sustainable Development and Globa...mentioning
confidence: 99%
“…Global seafood consumption has risen steadily since the 1950s (FAO, 2022), and ‘blue foods’ – marine life from both capture fisheries and aquaculture – are considered important for meeting the nutritional needs and dietary preferences of communities, countries, and cultures (Crona et al., 2023; Tigchelaar et al., 2022). Indeed, ending overfishing is a prerequisite for over half of Sustainable Development Goal (SDG) targets connected to SDG 14: Life Below Water (Singh et al., 2018), and equitable access to marine resources is considered a necessity for a viable blue economy (Cisneros‐Montemayor et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Seafood not only provides higher concentrations of essential nutrients than terrestrial animal-source foods (ASFs)8 but also prevents diet-related NCDs,9 10 as it is rich in two main omega-3 long-chain polyunsaturated fatty acids: docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), the intake of which may prevent IHD 11. The incidence of cardiovascular disease could be reduced by moderate consumption of seafood in many global North countries 12. Forage fish (ie, small pelagic fish of marine habitats, such as anchovies, herrings, and sardines, but excluding lake and other inland species) and salmon are recognised as excellent sources of DHA and EPA and are rich in essential micronutrients such as calcium and vitamin B12 10.…”
Section: Introductionmentioning
confidence: 99%